LATE ONSET MULTIPLE SCLEROSIS - Budimkić, Maja; Tamaš, Olivera; Veselinović, Nikola; Mesaroš, Šarlota; Drulović, Jelena (Medicinski podmladak, 2024)
Multiple sclerosis (MS) is an inflammatory demyelinating and neurodegenerative disease of the central nervous system (CNS) that usually occurs between the ages of 20 and 40. Less often, the diagnosis of MS can be made in children and adolescents, before the age of 18, as well as in people aged 50 and over. If the symptoms of MS appear in people aged 50 and over, this form of the disease is called late onset MS (LOMS). Compared to the classic onset of MS, people with LOMS are characterized by a more frequent occurrence of a progressive course of the disease, a delay in establishing a diagnosis in relation to the time since the appearance of initial neurological disorders, as well as a higher prevalence of motor disability. The older the person, the greater the risk of comorbidity, which negatively affects the course of the disease and potentially limits therapeutic options. There are limited data on the effectiveness and safety of therapy that modifies the natural course of the disease, for people with MS in this age group. It is particularly interesting how the aging process affects the pathophysiology of MS, the clinical course and the treatment approach of people with LOMS.